Context-aware goal-oriented business process modeling - Keriakos Sawers, Mariam Armia (AUC Knowledge Fountain, 2012)
Informed decision making and flexibility have grown to be important standard requirements in the field of business process modeling and design due to the emergence of intrinsically complex variables within the business environment. Traditionally, researches on business process modeling and informed decision making have focused on the configurability of business process models. Our review of literature made us realize that researchers in this field have considerably neglected the main drivers of flexibility and decision-making which have an extensive impact on business process flow. Such drivers form, in our opinion, cross cutting concerns that need to be extracted from within the context of the business process. Context can include, but is not limited to, work force availability, work force experience, system failures, weather conditions, environmental hazards, and financial constraints. In this research we present a new general purpose methodology for aspectized modeling of the context of business processes within the different business domains and also for modeling business processes as goal-oriented finite state machines. Being dependent on context-awareness and goal-orientation, our method deduces recommendations for improving the business process flow. We envisioned how context may be conceptualized, how contextual elements may be distributed across business operational levels according to the goals of the business process, and how business process flow recommendations based on the aspectized contextual facts may materialize. We managed to make our vision concrete by implementing all this into a prototypical framework that made the methodology both usable and testable. We tested our framework within the Airlines and Telecom business domains. The experimental results showed significant improvement in the financial costs and execution time. The results proved the importance of integrating context-awareness, context-modeling and goal-orientation in the field of business process modeling as well as configuration and decision making. By adopting context-awareness based on modern technology we believe that this research is a contribution in the field of intelligent business environments and that it opens the door for more challenging extensions on more complex goal-oriented business processes.